2019
DOI: 10.1111/jocd.12881
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive guide to upper lip aesthetic rejuvenation

Abstract: Summary The authors of this review present a comprehensive assessment of the techniques and indications in the treatment of the long upper lip. Setting aside the maxillofacial malformations, the review is focused on senescence as the most frequent etiology. A graphical reminder of the anatomical entities and of the upper lip proportions allows optimal preoperative planning. All current treatment options, from fillers to surgical excision and dermabrasion, are reviewed and summarized in order to provide an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Although aesthetic standards differ among different ethnicities and cultures, the universally recognized beauty of the lip is a proportionally larger upper lip with more protruding projection and a shorter philtrum. 5,6 Lip augmentation with hyaluronic acid, silicone, or fat such as vascular embolism and hypertrophic scar hinder the operative effect. 7,8 As a more minimally invasive treatment, conventionally, BTA is used to reduce the perioral wrinkles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although aesthetic standards differ among different ethnicities and cultures, the universally recognized beauty of the lip is a proportionally larger upper lip with more protruding projection and a shorter philtrum. 5,6 Lip augmentation with hyaluronic acid, silicone, or fat such as vascular embolism and hypertrophic scar hinder the operative effect. 7,8 As a more minimally invasive treatment, conventionally, BTA is used to reduce the perioral wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…Although aesthetic standards differ among different ethnicities and cultures, the universally recognized beauty of the lip is a proportionally larger upper lip with more protruding projection and a shorter philtrum 5,6 . Lip augmentation with hyaluronic acid, silicone, or fat graft restores the lip fullness.…”
Section: Discussionmentioning
confidence: 99%
“…The upper lip is delimited upwards by the nose, downwards by the mouth horizontal axis, and laterally by the nasolabial folds. 2 The upper lip has anatomical sub-units that need to be known and preserved when treating the lips with hyaluronic acid fillers.…”
Section: Second Step-lips Evaluationmentioning
confidence: 99%
“…Voluminous dry red lips are perceived as more attractive in several studies and a short upper white lip is highlighted as a criterion of beauty and youth. 2 On frontal view, an ideal height ratio of the midline upper to lower vermillion in white individuals has been previously defined as 1:1.6 based on the golden ratio. 2,4,5,6 This can vary with patient desire and ethnicity and some studies reported that this ideal ratio can range between 1:1 and 1:1.6 with a ratio closer to 1:1 being more suitable for individuals of African ethnicity.…”
Section: Second Step-lips Evaluationmentioning
confidence: 99%
See 1 more Smart Citation